PERAN MEDIA SOSIAL DALAM MENDORONG PARTISIPASI POLITIK PEMILIH PEMULA DI KECAMATAN DUNGALIYO PADA PEMILU 2024 - Olii, Delya Putri; Hamim, Udin; Mahmud, Ramli (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to analyze the role of social media in encouraging political participation among first-time voters in Dungaliyo Sub-district during the 2024 General Election. Social media has become the primary channel for disseminating political information, especially among the younger generation with extensive access to digital technology. This research employed a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The research subjects consisted of 15 first-time voters who were active users of social media platforms such as Instagram, TikTok, and Facebook. The findings reveal that social media plays a significant role in increasing political literacy, shaping political attitudes, and encouraging active participation in the electoral process. Social media functions as a source of political information, a means of political education, and an effective space for political discussion. Factors influencing the political participation of first-time voters include political stimuli, personal characteristics, and social environmental influences. These findings highlight the importance of optimizing the use of social media as a political education tool to enhance the quality of democratic participation among young people in rural areas. ABSTRAKPenelitian ini bertujuan untuk menganalisis peran media sosial dalam mendorong partisipasi politik pemilih pemula di Kecamatan Dungaliyo pada Pemilu 2024. Media sosial kini menjadi saluran utama penyebaran informasi politik, khususnya bagi generasi muda yang memiliki akses luas terhadap teknologi digital. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data berupa observasi, wawancara mendalam, dan dokumentasi. Subjek penelitian terdiri dari 15 pemilih pemula yang aktif di platform media sosial seperti Instagram, TikTok, dan Facebook. Hasil penelitian menunjukkan bahwa media sosial memiliki pengaruh signifikan dalam meningkatkan literasi politik, membentuk sikap politik, serta mendorong partisipasi aktif dalam proses pemilu. Media sosial berperan sebagai sumber informasi politik, sarana edukasi politik, dan ruang diskusi politik yang efektif. Faktor-faktor yang memengaruhi partisipasi politik pemilih pemula meliputi perangsang politik, karakteristik pribadi, dan pengaruh lingkungan sosial. Temuan ini menegaskan pentingnya optimalisasi penggunaan media sosial sebagai instrumen edukasi politik yang mampu meningkatkan kualitas partisipasi demokratis di kalangan generasi muda di daerah.